Arctic Forecasting: Formation of a Research Field - Alexander V. Kotov (Арктика и Север)
In the domestic literature, there are still not enough works devoted to a comprehensive description of the phenomenon of Arctic forecasting. This article distinguishes it from the general socio-economic context. The analysis of foreign studies on Arctic forecasting technologies and key factors allowed us to reveal the research question: can Arctic forecasting be considered a highly specific area? The work has examined physical-geographical and resource factors: climate, maritime transport, ice cover, oil production and others. Studies demonstrating the interrelation of factors were widely used: for example, climate and energy, social and economic changes. Based on the authors’ approaches, a typology of Arctic forecast models has been developed, taking into account the number of variables considered and the quantitative-qualitative nature of the specifications. In the course of analyzing the dynamics of the research agenda of the European symposium “The Future of the Arctic”, the evolutionary formation of the topic of Arctic forecasting is shown. The main feature is its reliance on resources as the basic essence of the Arctic economy. It is shown that the involvement of Arctic resources in the economic turnover depends on the world technological dynamics: through natural resources the Arctic economy is connected with the world economic processes. The phenomenon of Arctic forecasting includes a more merged, multitasking nature of natural-climatic and economic modelling than standard models for studies of environmental dynamics, with forecasting of positive and adverse social and economic consequences. The presented results structure the phenomenon of Arctic forecasting for the development of methodological approaches to substantiate the prospects for the development of polar and northern regions. The considered factors will be useful in developing state policy measures in relation to the Arctic zone of the Russian Federation.